A study of the relationship between leadership style and employee turnover intention in Shanghai, China - Wen, Xin Tian (2007)
Leadership is the process of influencing others to facilitate the attainment of organizationally relevant goals. The general objective of this research is to determine the impact of transformational-transactional leadership style and leadership factors have any effect on employee turnover intention in Shanghai, China. The paper reviews the basic theory and former researches on to what extent these factors have effect on employee turnover intention. The sample of this study comprise of the staff, first line managers and middle managers in Shanghai. A sample of 230 participants was targeted; and 171 questionnaires, which were utilized as the main instrument in this study, were returned. Eight hypotheses were constructed and testing by SPSS program of multiple regressions. And it was found out that both transformation and transactional leadership style had a significant relationship with employee turnover intention. Leadership factor inspirational motivation had a negative impact on employee turnover intention, and factor passive manage-by-exception and laissez-faire had positive impact on employee turnover intention.